Biodegradation of hydrocarbon from bottom oil tanks - Pucci, Graciela (2015)
Oil bottom tank sludge is an environmental problem to be solved in the Gulf San Jorge basin. In this paper we study the biodegradation of hydrocarbon remaining in the sediment after washing with water and detergent of the oil bottom tanks. Bioreactors were made to which the system followed by OxiTop, oxygen consumption, and bacterial counts were carried hydrocarbon determination infrared (IF) and by gas chromatography (GC). The sediment from the background wash tank contained enough degrading and total aerobic bacteria, with a predominance of the genera Pseudomonas sp. and Rhodococcus sp. Microbial population, and the condition of 20% humidity, oxygen and nutrients in a ratio of 100: 3: 03 showed an decreased from 2.9 to 0.4% of hydrocarbon with a strong used of linear alkane (13 to 26C) and less used of aromatic.